SINEMATIK TEROR: EKSEPSIONALISME AMERIKA DAN PROPAGANDA ANTI-ISLAM DALAM FILM 12 STRONG - Sekar Yolanda Azza; Yusrina Dinar Prihatika (Haluan Sastra Budaya, 2021)
The concept of American exceptionalism in American cinema is a way for propagandists to instill certain values or doctrines in the audience. This is clearly depicted through the narrative and non-narrative aspects where each dialogue, characterization, setting and also the way the camera take a shot reflects an effort of exceptionalism that is implanted throughout the film. These efforts led to the practice of propaganda against Islam and Muslim. By using a descriptive analysis method described using binary opposition theory, this research reveals the existence of American exceptionalism indoctrination which has an impact on the emergence of anti-Islamic ideology. The existence of a propaganda technique that is reflected in the film, such as card stacking, creates a cinematic terror in the film about the depiction of Middle Eastern people, especially Muslims.